Effect Of Multi-Wall Carbon Nanotubes On The Performance Of Self-Healing Rubber - Ang, Chai Pin (Universiti Sains Malaysia, 2022)
In order to meet the requirement of final product, natural rubber need to be crosslinked to form 3D covalent network. However, the vulcanization process turns the gum rubber to act like thermoset with the impossibility to self-heal. From the view point of sustainable development of rubbers, it is substantial to integrate the self-healing capability into commercial rubber. The mechanical performance of self-healing rubber need to be enhanced through addition of filler in order to fulfil the demand. This study aimed to assess and investigate the effect of multi-wall carbon nanotubes on the properties of self-healing rubber compound. In this work, different amount of multi-wall carbon nanotube was added into the self-healing NR in order to assess the effect of multi-wall carbon nanotube on the heal ability and mechanical performance. It was found that the tensile strength and tear strength increased with the multi-wall carbon nanotube content. The addition of multi-wall carbon nanotube increased the crosslink density of the self-healing NR compound. The roughness at the fracture area was increased as observed using scanning electron microscope. From SEM images, a small gap was observed at the cut line for NR with 6 phr of multi-wall carbon nanotube which may be due to the addition of multi-wall carbon nanotube reduced the reaction between PZT radical with zinc thiolate and rubber molecules as the multi-wall carbon nanotube content increased. The results also revealed that the self-healing NR with 6 phr of multi-wall carbon nanotube have the highest storage modulus. Addition of MWCNT also increased the payne effect of the NR compound. The conductivity of self-healing NR compound increased with the content of multi-wall carbon nanotube. The results of DSC showed that the glass transition temperature stay unaltered within the presence of multi-wall carbon nanotube which was believed that the presence of filler has no effect on the glass transition temperature.